The Role of University Support Services in Addressing Mental Health Challenges: A Narrative Review - Satriono, Ferry Damarjata; Seghatoleslam, Tahereh; Habil, Hussain; Wishwadewa, Winny Nurhajati (The Indonesian Institute of Science and Technology Research, 2025)
University students face significant mental health challenges, including anxiety, depression, and stress, which may negatively impact their academic performance and overall well-being. This narrative review explores the important role of university support services in addressing these challenges. Services such as on-campus counselling, wellness programs, and peer support initiatives are vital in providing professional guidance, coping strategies, and fostering a supportive environment. It also highlights barriers to accessing these services, including stigma, long wait times, and cultural or socioeconomic factors, which can affect students from seeking help. Innovative approaches like digital platforms, teletherapy, and holistic wellness programs can enhance accessibility and engagement. The review identifies research gaps, particularly regarding the long-term impacts of mental health services on academic success. Recommendations emphasize the importance of culturally competent care, collaboration with faculty and staff, and ongoing evaluation to improve service delivery. By prioritizing mental health services and adopting innovative strategies, universities can better support their students, reduce stigma, and promote help-seeking behaviours. This review calls for institutions to expand and improve their mental health programs to meet their students' diverse and growing needs.